(untitled) (Research, Society and Development, 2022)
Münchausen Syndrome by Proxy occurs when a caregiver lies about the health of the person in their care. This study aimed to synthesize the results obtained in publications about this syndrome, aiming at its greater understanding by listing the characteristics of the victims, the aggressor’s motivation, the signs and symptoms that allow its diagnosis, as well as the recommendations to health professionals and specialists about the diagnosis. precocious. This is an integrative literature review using a form as an instrument for data collection in 15 publications from 2019 to 2022. It was found that most publications (81.25%) occurred in the medical field; the methodological characteristics were a literature review, followed by a case report associated with clinical experience; the victims were children up to 12 years old, regardless of sex; the aggressors, in the vast majority, are mothers with a history of abuse and emotional disorders, with no apparent or relevant motivation and many are health professionals. The signs and symptoms presented by the victims are nonspecific and intermittent, which makes early diagnosis difficult and requires constant attention from health professionals to the warning signs shown by the victim and present in the aggressor’s behavior. Early diagnosis of this syndrome is a challenge because its symptoms depend on the factitious story told by the aggressor. However, the difficulty of clinical recognition of patients with this syndrome is minimized when health professionals are aware of this possibility and work in a multidisciplinary way.